Safety and efficacy of elsubrutinib or upadacitinib alone or in combination (ABBV-599) in patients with rheumatoid arthritis and inadequate response or intolerance to biological therapies: a multicentre, double-blind, randomised, controlled, phase 2 trial. (June 2022) - Fleischmann, Roy; Friedman, Alan; Drescher, Edit; Singhal, Atul; Cortes-Maisonet, Gregorio; Doan, Thao; Lu, Wenjing; Wang, Zailong; Nader, Ahmed; Housley, William; Cohen, Stanley; Taylor, Peter C; et al.
Summary: Background: ABBV-599 is a novel fixed-dose combination of the Bruton's tyrosine kinase (BTK) inhibitor elsubrutinib and the Janus kinase (JAK) inhibitor upadacitinib under investigation for the treatment of autoimmune diseases. We aimed to determine whether ABBV-599 could increase the treatment response for patients with active rheumatoid arthritis compared with inhibiting either pathway alone, while maintaining an acceptable safety profile. Methods: We conducted a multicentre, double-blind, parallel-group, dose-exploratory, randomised, controlled, phase 2 trial at 75 community sites in eight countries in Europe and North America. We enrolled patients who were 18 years or older with rheumatoid arthritis and inadequate response or intolerance to biological disease-modifying antirheumatic drugs. Eligible patients were randomly assigned (3:2:2:2:2:1) via interactive response technology to receive daily, orally administered ABBV-599 (ie, upadacitinib 15 mg plus elsubrutinib 60 mg), elsubrutinib 60 mg, elsubrutinib 20 mg, elsubrutinib 5 mg, upadacitinib 15 mg, or placebo. Randomisation was stratified by the number of previous biological disease-modifying antirheumatic drugs. The investigator, study site personnel, and patients were masked throughout the study. The primary endpoint was change from baseline in disease activity score of 28 joints with C-reactive protein (DAS28-CRP) at week 12 for all patients who received a study drug. Pharmacokinetics and safety were also assessed. This study is registered with ClinicalTrials.gov, number NCT03682705 . Findings: Between Oct 8, 2018, and March 26, 2020, 242 patients were randomly assigned to receive ABBV-599 (n=62), elsubrutinib 60 mg (n=41), elsubrutinib 20 mg (n=39), elsubrutinib 5 mg (n=41), upadacitinib 15 mg (n=40), or placebo (n=19). Of the 242 patients, 204 (84%) were female, 38 (16%) were male, and 220 (91%) were White; the mean age at baseline was 58·0 years (SD 11·3). Compared with placebo, the least squares mean changes from baseline in DAS28-CRP were –1·44 (90% CI –2·03 to –0·85; p<0·0001) for ABBV-599, –0·40 (−1·03 to 0·23; p=0·29) for elsubrutinib 60 mg, –0·20 (−0·85 to 0·44; p=0·61) for elsubrutinib 20 mg, –0·21 (−0·84 to 0·41; p=0·57) for elsubrutinib 5 mg, and –1·75 (−2·38 to –1·13; p<0·0001) for upadacitinib. No significant improvements in efficacy measures for elsubrutinib alone (any dose) versus placebo were detected, despite adequate plasma exposure and target engagement. Treatment-emergent adverse events were observed in 113 (47%) of 242 patients, with similar proportions for all groups. Interpretation: Significant improvements in disease activity metrics of rheumatoid arthritis with ABBV-599 were driven by the JAK inhibitor upadacitinib with no discernible effect by the BTK inhibitor elsubrutinib. Funding: AbbVie.